Evaluation of the Drying Kinetics of the Cake from Linseed Oil Extraction - dos Santos, Casi Santos; Rolim, Amanda Heloize; Afonso, Eliza Taborda; de Camargo, Marina Raquel Bento; Miranda, Rebeca Becker; Johann, Gracielle; Montanher, Paula Fernandes (Orbital: The Electronic Journal of Chemistry, 2019)
Considering that drying is one of the oldest unit operations, and widely used in the preservation of biological products, the present study evaluated the drying kinetics of the cake obtained from linseed oil extraction. The samples were submitted to forced air circulation drying oven under temperatures of 40, 50, 60, 70 and 80 ± 1 °C. Simplified mathematical models were adjusted (Verna, Page, Newton, Henderson and Pabis, Two terms and Modified Page) to describe the drying kinetics of the by-product. It was observed that the drying time was dependent on both temperature and relative humidity of the drying air. The ‘Two Terms’ model was the best fit to the experimental temperature data measured, with highest range of coefficient of determination (0.97-0.99) and smaller range of root-mean-square error (between 1.96x10-4 and 5.69x10-4). The standard error of prediction ranged from 1.86x10-2 to 7.94x10-2 and the average of relative standard deviation was the lowest observed (14.97). Thus, from the experimental data and adjusted parameters from the ‘Two Terms’ model, it is possible to predict the drying behavior in the temperature range studied.DOI: http://dx.doi.org/10.17807/orbital.v11i6.1247